PRACTICAL ASPECTS OF APPLYING DIFFERENT LEGAL TRADITIONS IN INTERNATIONAL ARBITRATIONS - Драган Зелић; Ненад Барош (Годишњак Правног факултета у Бањалуци)
There is no unified and comprehensive definition of arbitration in legal science.3 Most of the positive regulations that regulate it, both in the world and in our country (the Arbitration Act), omit the issue of its definition. However, in science and in legal practice, arbitration is most often defined through arbitration dispute, its elements, course and legal effects, and through indicating differences between arbitration and judicial process, i.e., arbitration and other alternative dispute resolution methods. It is concluded that arbitration is an alternative to judicial settlement of a dispute, formed by consensus or consent of the will of the parties involved, private, and that its decisions are legally binding and final.4 5 This paperwork is trying to explain differences and different way of conducting in case when participants in arbitration cases are from different legal systems, especially differences between the most important and the most spreader legal systems in the world, European, civil law system and Anglo-Saxon law (common law). In the second and third chapter, attention is paid to the procedural and material differences between the continental and the common law arbitration procedures, especially in differences between the investigative (continental legal system) and the common law principles of the proceedings. In the fourth chapter, the difference between the starting of the arbitration procedure was dealt with, while in chapter five, special attention was paid to the presentation of evidence in the mentioned legal systems. The witnesses and expert witnesses deal with the sixth and seventh chapters of the paper, while the question of the privacy of the dispute is left behind for the last chapter of the paper, followed by a conclusion.